Current analysis of hypoxic-ischemic encephalopathy research issues and future treatment modalities - She, Hong-Qing; Sun, Yi-Fei; Chen, Li; Xiao, Qiu-Xia; Luo, Bo-Yan; Zhou, Hong-Su; Zhou, Di; Chang, Quan-Yuan; Xiong, Liu-Lin (Frontiers in Neuroscience, 2023)
Hypoxic-ischemic encephalopathy (HIE) is the leading cause of long-term neurological disability in neonates and adults. Through bibliometric analysis, we analyzed the current research on HIE in various countries, institutions, and authors. At the same time, we extensively summarized the animal HIE models and modeling methods. There are various opinions on the neuroprotective treatment of HIE, and the main therapy in clinical is therapeutic hypothermia, although its efficacy remains to be investigated. Therefore, in this study, we discussed the progress of neural circuits, injured brain tissue, and neural circuits-related technologies, providing new ideas for the treatment and prognosis management of HIE with the combination of neuroendocrine and neuroprotection.